Problems of Providing Primary Health Care and Prospects for Their Solutions - o'g'li, Naimov Dilshod Qayim (Journal of Science in Medicine and Life, 2024)
Primary health care offers a cost–effective route to achieving universal health coverage (UHC). However, primary health-care systems are weak in many low- and middle-income countries and often fail to provide comprehensive, people-centred, integrated care. We analyzed the primary health-care systems in 20 low- and middle-income countries using a semi-grounded approach. Options for strengthening primary health-care systems were identified by thematic content analysis.